Erstellung und Verwendung eines Grafiksystems für das Gressoneyer Titsch: Zwischen Standard- und Spontanschrift - Caterina Saracco (Linguistik Online)
This paper explores the history of the efforts to establish a codified and transferable orthographic system for the Titsch language of Gressoney, an idiom of Alemannic origin spoken in Italy. It also examines the unique characteristics of spontaneous writings (cf. Dal Negro/ Guerini/Iannàccaro 2015: 32f.) by elderly native speakers. Although Titsch is their first language (L1), these individuals now predominantly use Italian for both written and oral communication. The analysis highlights how Italian orthographic norms have increasingly influenced Titsch writing, largely due to an incomplete understanding of the language’s standard orthography. This lack of knowledge stems from the absence of formal education in Titsch. Indeed, no members of the Walser community have been formally taught to write in their Germanic variety according to a orthographic norm.